Driver brake vs. steer response to sudden forward collision scenario in manual and automated driving modes. (February 2017) - Blommer, Mike; Curry, Reates; Swaminathan, Radhakrishnan; Tijerina, Louis; Talamonti, Walter; Kochhar, Dev
Highlights: Situations may arise in automated driving where the driver is required to re-engage. Three driving scenarios were investigated; 2 autonomous, 1 manual. Forty-eight volunteers participated in a simulator study conducted in VIRTTEX. At handoff, for both autonomous scenarios, drivers reaction times were longer than manual driving. Results suggest that drivers may benefit from appropriate ADAS technologies. Abstract: In autonomous vehicle operation, situations may arise when the driver is required to re-engage in manual control of the vehicle. Whether the control handoff from vehicle to human is done in a structured or unstructured manner, the process may be affected by the driver's state, i.e. distracted or not. The study reported here was designed to measure a non-distracted driver's response to a sudden forward collision (FC) event, in which the driver would assume manual control of the autonomous vehicle. Three driving scenarios were investigated: autonomous vehicle driven with full collision avoidance support, autonomous vehicle driven without collision avoidance support, and vehicle driven in manual mode. Forty-eight volunteers participated in a simulator study conducted in VIRTTEX. It was found that, at handoff, (1) drivers in manual mode tended to use evasive steering, rather than braking, compared to drivers in both the autonomous modes, (2) between subjects variations in speed were higher for the automation with collision support condition than for the other two scenarios, (3) for both autonomous driving scenarios, drivers reaction times were longer than for manual driving. In some cases the driver response was so late and the distance remaining so reduced that crash avoidance might be unfeasible. At a minimum, results of this study suggest that drivers may benefit from appropriate driver assistance technologies when a crash imminent situation is suddenly encountered.